2006
DOI: 10.1007/s10637-006-5938-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of DNA methyltransferase 1 inhibition with the antisense oligonucleotide MG98 in patients with metastatic renal carcinoma: A National Cancer Institute of Canada Clinical Trials Group investigational new drug study

Abstract: DNA methyltransferases (DNMTs) methylate DNA, promoting local chromatin condensation and consequent repression of gene expression. The purpose of this two-stage phase II trial was to assess the antitumor activity of MG98, a second generation antisense oligodeoxynucleotide inhibitor of human DNMT 1, in patients with metastatic renal carcinoma (MRC). Untreated adult patients with measurable MRC were treated with MG98 at a dose of 360 mg/m2 via 2-h iv infusion twice weekly for three consecutive weeks out of four.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 21 publications
(21 reference statements)
1
65
0
1
Order By: Relevance
“…The number of courses and cumulative dose received are summarized in Table 2. The adverse event profile reported across the dose levels in this trial was similar to that reported in other clinical trials with MG98 (20,23,24). Compiled grade 3 and 4 adverse events, including those commonly observed in patients with MDS and AML and therefore non -dose limiting, are detailed in Table 3.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The number of courses and cumulative dose received are summarized in Table 2. The adverse event profile reported across the dose levels in this trial was similar to that reported in other clinical trials with MG98 (20,23,24). Compiled grade 3 and 4 adverse events, including those commonly observed in patients with MDS and AML and therefore non -dose limiting, are detailed in Table 3.…”
Section: Resultssupporting
confidence: 73%
“…Similar to other studies with MG98, the most common toxicities were fatigue and fever, and asthenia that led to patient withdrawal from the study (20,23,24), which prevented us from further escalating MG98 that may have produced greater target down-regulation. This toxicity profile is similar to that observed with other phosphothiorate compounds, where improvements in tolerability were described once different administration schedules were adopted (20 -24).…”
Section: Discussionmentioning
confidence: 71%
“…100,101 The best-tolerated protocol was chosen for phase II studies but, unfortunately, did not show any antitumoral activity in patients with metastatic renal carcinoma. 102 In a recent phase I trial, MG98 has been also tested for the treatment of patients with high-risk MDS and AML. Even in this case, this approach failed to result in appreciable effects, and the dose escalation was stopped due to severe toxicity.…”
Section: Dnmt Silencingmentioning
confidence: 99%
“…To date, the most widely used chromatin remodeling drug is the DNA methyltransferase inhibitor 5-aza-2 ¶-deoxycytidine (5-aza-2 ¶-dC), recently approved for therapeutic treatment (15). Several methyltransferase inhibitors [such as 5-aza-dC and MG98 (16,17)] and HDAC inhibitors [such as suberoylanilide hydroxamic acid (SAHA; ref. 18), valproic acid (19), and pivaloyloxymethyl butyrate (20,21)] are presently in phase I and II clinical trials.…”
Section: Introductionmentioning
confidence: 99%